PENERAPAN TEAM GAMES TOURNAMENT (TGT) DALAM UPAYA MENINGKATKAN KREATIVITAS DAN MINAT BELAJAR PADA STANDAR KOMPETENSI PROSES PENGELOLAAN KREDIT - Mariyaningsih, Nining (Dinamika Pendidikan, 2010)
The objectives of this study are: (1) to know the effectiveness of Team Games Tournament (TGT) method to improve the accounting creativity learning for accounting students in SMK Negeri 1 Salatiga (2) to know the improvement of students’ interest in accounting learning through Team Games Tournament (TGT) method in SMK Negeri 1 Salatiga, and (3) to know the improvement of students’ creativity and learning interest through Team Games Tournament (TGT) method in SMK Negeri 1 Salatiga. This study was class action research which was designed into three main cycles; they were 1st cycle, 2nd cycle and 3rd cycle.  Each cycle consisted of four stages started from planning - implementation - evaluation - analysis and reflection. The study was conducted for XI class in SMK Negeri 1 Salatiga. The collected data were: (1) students' activities during learning, (2) teacher and students’ interaction, (3) the level of students' creativity and interest, (4) student achievement and (5) students' response toward the learning process. The observation of learning process was conducted by the collaborators. The result showed that the good quality of learning process was if teachers were able to motivate students to learn actively and creatively. After analyzing the data, it showed that the students’ activeness to raise the new ideas was up to 91% while the students’ activeness to join the discussion group was only 84%. Then, the students’ enthusiasm in joining the game was up to 95%, it meant that the students were very interested in the game. In the first cycle, the students’ learning mastery increased from 24% to 62%, the increase of the second cycle was 8%. And finally, in the third cycle, it increased significantly by 22%. Thus; it can be concluded that the cooperative learning model with TGT type can improve students' understanding on the concepts learned.